Aqueous Surfactant‐Based Extraction of Cottonseed Collets from an Industrial Oilseed Processing Facility. (10th June 2017) - Petts, Alexander J.; Hou, Lili; Sabatini, David A.; Kibbey, Tohren C. G.
Abstract: While cotton is largely produced for its fibers, the seed and hull byproducts are essential for agricultural economies around the world for their high oil content and wide range of uses. Cottonseed oil is often extracted by solvent extraction, a process that is of increasing concern due to its potential to impact human and ecological health. For this reason, environmentally‐benign extraction methods are increasingly being explored. The focus of this work is on aqueous surfactant‐based extraction of cottonseed collets taken directly from a conventional solvent‐based extraction facility. A propoxylated–ethoxylated extended anionic surfactant was tested for its ability to extract cottonseed oil. Results found that moderate (77%) extraction yields could be achieved by the surfactant given adequate surfactant concentration (0.5% in this case). However, unlike previous work with other oilseeds, the best extractions were achieved at moderate interfacial tensions (0.2–3.0 mN/m); surfactant formulations capable of producing ultralow interfacial tensions led to much lower extraction yields, as did water‐only extraction. Similar behavior was also observed for two different conventional surfactants, with decreasing interfacial tension values below 0.1 mN/m leading to decreasing yields for all surfactants tested.